Kadar IL-10 Mencit Balb/C Terinfeksi Plasmodium berghei dengan Pemberian Fraksi Metanol Bangle (Zingiber cassumunar Roxb.) sebagai Terapi Komplementer (The IL-10 level of Plasmodium berghei-infected Balb/C Mice after Methanolic Fraction of Bangle (Zingib - Asis Fitriana; Bagus Hermansyah; Muhammad Afiful Jauhani; Wiwien Sugih Utami (Pustaka Kesehatan, 2018)
Malaria is an infectious disease caused by Plasmodium spp. The cause of mortality in malaria is the parasite’s resistance to malaria drugs and immune system problem. Interleukin-10 is an anti-inflammatory cytokine during plasmodium infection. Bangle is a herbal remedy that contains high amount of curcumin showing immunostimulant activity. The purpose of this study was to determine the difference of IL-10 level in Plasmodium berghei-infected Balb/C mice given with methanolic fraction of bangle (Zingiber cassumunar Roxb.) as a complementary therapy. This study was a true experimental with posttest control group design using 25 mice Balb/c which divided into 5 groups (A, B, C, D and E). All groups except group A were infected with P. berghei. After positively infected, group B was not treated, C was treated with artemisinin, group D was given with artemisinin and methanolic fraction bangle 0,017 mg/gBW, group E was treated with methanolic fraction bangle 0,017 mg/gBW. The result showed that group D had the highest-level of IL-10 among the treatment groups. The Post Hoc LSD test showed p value ≥ 0,05. In conclusion, there was no significant difference of IL-10 serum level in P. berghei-infected Balb/C mice given with methanolic fraction of bangle (Z. cassumunar Roxb.) as complementary therapy. Keywords: Interleukin-10, Plasmodium berghei, Bangle (Zingiber cassumunar Roxb.)